A novel approach to extend microbiological stability of sea bass (Dicentrarchus labrax) fillets coated with electrospun chitosan nanofibers - Ceylan, Zafer; Sengor, Gulgun F. Unal; Sagdic, Osman; Yilmaz, Mustafa Tahsin (ELSEVIER SCIENCE BV, 2017)
We tested electrospun chitosan nanofibers (CN) and liquid smoke-loaded electrospun chitosan nano fibers (LSCN) in terms of limitation of Total Mesophilic Aerobic Bacteria (TMABc), Psychrophilic Bacteria (TPBc) and Yeast and Mold count (YMc) growth during storage period. CN and mixtures of CN and LS were electrospun to yield smooth, cylindrical, beadless and ultrafine polymeric nanofibers. Molecular (Fourier Transform Infrared Spectroscopy, FTIR), thermal (Thermogravimetric Analysis, TGA), zeta potential (Dynamic Light Scattering, DLS) and surface (Scanning Electron Microscopy, SEM) properties of CN and LSCN were determined. FTIR results revealed that the LS could be encapsulated within chitosan nanofibers. SEM images showed a smooth structure. TGA indicated thermal decomposition (a reduction in mass of CN and LSCN at temperatures below 150 degrees C, corresponding to 11.8 and 10.77%, respectively) and DLS demonstrated dispersion stability (1 potential +22.3 and +27.1 mV for CN and LSCN, respectively) properties. Microbiological stability tests demonstrated that CN and LSCN were both effective against growth of the tested microorganisms, exhibiting almost 40-50% limitation of growth; but the antimicrobial effect of CN was more than that of LSCN. The results suggested that coating of the fish fillets with the nanofibers would be a promising technique to limit microbial growth in fish fillets. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial surface-coating material; Electrospun nanofiber; Encapsulation; Liquid smoke; Fish; IN-VITRO; NANOPARTICLES; MEMBRANES; DELIVERY; QUALITY; Food Science & Technology